STRATEGI PENGEMBANGAN POTENSI WISATA BAHARI DI PANTAI CRYSTAL BAY DESA SAKTI, KEC. NUSA PENIDA, KAB. KLUNGKLUNG - Sastrawan, I Gede Anom; Sunarta, I Nyoman (JURNAL DESTINASI PARIWISATA; Vol 2 No 2 (2014): VOL 2, NO 2 (2014): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2014.v02.i02.p09, 2014)
ABSTRACT The study aims to determine Strategy Development the potency of the Crystal Bay Beach as a tourist attraction in the village of Sakti marine, Nusa Penida district. Klungkung and how the development of appropriate strategy to overcome obstacles in the development of Crystal Bay Coast region as a Marine Tourism attraction in Village Sakti, Nusa Penida district Klungkung. Through the use of method data analys of SWOT (Strength, Weaknesses, Opportunities, Threats) acquired programs attempt to do, among other things : short-term planning include : the creation of support facilities, physical arrangement, the arrangement of the surrounding environment, creation of parking areas and conducting outreach to the community and long-term planning include : utilization of space, the arrangement of the HR ( Human Resources ) as well as a promotion of Crystal Bay Beach. Constraints faced by among others ; Human Resources, Lack of Awareness Local to feel ownership for the appeal of Crystal Bay Beach, lack of promotion, lack of Supporting Facilities, Transit Fascination Advice to the parties concerned to develop a Crystal Bay Beach in particular local government and local communities to realize the development of nautical tourism attraction in Crystal Bay Beach, provide education and training on tourism to the community, to support the utilization of the potential appeal of Crystal Bay Beach adjusted to detailed directives in the field and increase the network to promote tourism , especially in Klungkung.
Keywords: Strategy Development, Potency, Marine Tourism